(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2020)
Nitrate grown cultures of the two cyanobacterial strains were broken into unicells and homogenized. Equal amount of the cultures was inoculated in test tubes containing 10 ml liquid media and incubated in growth chamber for 30 days. Growth was recorded alternate day and it was found that the two algae have almost identical log and lag phase of growth. Lag phase of the growth was found to be 2-4 days whereas log phase period of the growth was achieved on 24 - 28th day of inoculation. Nostoc musocorum appeared to attain log phase earlier than Anabaena variabilis. However, for both the algae growth appeared to be stationaiy or declining after 24th day of inoculation. Therefore, 24th day was taken as the log period of the growth for the two algae.